2022
DOI: 10.1038/s41377-022-00856-y
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-doped phosphorescent carbon dots for grayscale patterning

Abstract: Flexible organic materials that exhibit dynamic ultralong room temperature phosphorescence (DURTP) via photoactivation have attracted increasing research interest for their fascinating functions of reversibly writing-reading-erasing graphic information in the form of a long afterglow. However, due to the existence of a nonnegligible activation threshold for the initial exposure dose, the display mode of these materials has thus far been limited to binary patterns. By resorting to halogen element doping of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Organic materials with room-temperature ultralong phosphorescence have been receiving increasing attention due to their merits of low cost, low toxicity, flexible structural modification, and facile color tuning and their wide applications in bio-imaging/sensing, encryption/anti-counterfeiting, organic light-emitting devices, etc. Screening the literature, we can find that guest–matrix systems play a vital role in promoting room-temperature ultralong organic phosphorescence (RTUOP). Particularly, 1 H -benzo­[ f ]­indole/carbazole (Bd/Cz) guest–matrix systems, where Bd derivatives and Cz derivatives function as the guest and the matrix, respectively, have been widely studied in the past several years. In our previous work, it is revealed that Bd or its derivatives show (photo-activated) RTUOP in polymers such as PMMA or solid powders such as 4-(dimethylamino)­pyridine (DMAP) and Cz derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials with room-temperature ultralong phosphorescence have been receiving increasing attention due to their merits of low cost, low toxicity, flexible structural modification, and facile color tuning and their wide applications in bio-imaging/sensing, encryption/anti-counterfeiting, organic light-emitting devices, etc. Screening the literature, we can find that guest–matrix systems play a vital role in promoting room-temperature ultralong organic phosphorescence (RTUOP). Particularly, 1 H -benzo­[ f ]­indole/carbazole (Bd/Cz) guest–matrix systems, where Bd derivatives and Cz derivatives function as the guest and the matrix, respectively, have been widely studied in the past several years. In our previous work, it is revealed that Bd or its derivatives show (photo-activated) RTUOP in polymers such as PMMA or solid powders such as 4-(dimethylamino)­pyridine (DMAP) and Cz derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…, both solid state fluorescence and in-room RTP. It is more interesting to note that FCDs–CMCNa exhibits special temperature-sensitive optical properties when the temperature is reduced from 300 K to 90 K. It exhibits an increase in fluorescence/phosphorescence intensity with decreasing temperature up to the switching point of 150 K, which then gradually decreases with decreasing temperature to 90 K. Later, Liu et al 142 proposed a series of flexible dynamic ultra-long RTP polymer composites, which are illuminated by halogen doped CDs and have fully programmable emission. They had produced a transparent, flexible and fully programmable dynamic ultra-long RTP composite film with reliable gray-scale display ability from the synthesized RTP material for the first time.…”
Section: Annual Representative Studies On Cd-based Rtp Materialsmentioning
confidence: 99%
“…When they anchored on the surface of the C-dots, various matrices were required to immobilize the external n –π* emissive center for activating RTP. Reversely, if these groups were embedded in the interior of C-dots, the internal hydrogen bonds and polymer-like covalent bonds of C-dots as self-matrices can “lock” the internal triplet excitons, efficiently suppressing the nonradiative relaxation. Therefore, long-lived afterglows in the exterior and interior of the C-dots were observed. Two types of matrix-free RTPs of the C-dots were fabricated due to the low energy gap between S 1 and T 1 (Δ E ST ) , and heavy atom effect. Unfortunately, many C-dots-based RTPs can be observed in the solid state because these C-dots are highly hydrophilic and easily infiltrated by water containing dissolved oxygen, resulting in the insufficiency of RTP in aqueous solution . Thus, the activation of long-lived RTP in the aqueous environment remains a tremendous challenge, and more attention has been drawn to establish self-protective RTP of C-dots.…”
Section: Introductionmentioning
confidence: 99%